Bridge strengthening and rehabilitation - Petros P Xanthakos (Prentice-Hall, 1996)
The book presents the methodologies used by states and general agencies to identify the bridge needs and prioritize projects eligible for maintenance, improvement, or replacement; reviews procedures used to assess bridge deficiencies; introduces the fundamentals of structural capacity analysis to assess the overall structure adequacy of existing bridges; identifies the usual problems and defects of bridge components; and reviews the methods and techniques used to implement repairs, strengthening, retrofiting, rehabiliting, replacement, and related improvements